Obtaining okra hybrids through partial diallel analysis - Silva,Edgard Henrique Costa (2021)
Abstract The exploration of heterosis can be an efficient alternative to increase okra yield. The partial diallel strategy optimizes resources by guiding crosses based on genetic diversity between various genotypes. This study aimed to identify potential hybrid combinations through diallel analysis in comparison with commercial cultivars. The hybrids were evaluated by means of a partial diallel scheme based on the genetic divergence of the genotypes. Fourteen hybrids and their reciprocals were evaluated in the winter and summer conditions of Jaboticabal - SP for yield, number of fruits and precocity. No line showed significant general combining ability. The reciprocal effect was not significant for the evaluated characteristics. Four hybrid combinations showed significant and positive specific combining ability for number of fruits, which were considered promising hybrids. In the winter, the experimental hybrids 1 x 8 and 3 x 8 showed superior performance compared to the commercial hybrids. No significant differences were observed in the summer.